Characterization Of A Thermostable Lipase From Aneurinibacillus Thermoaerophilus Strain Hz - Masomian, Malihe (2007)

(untitled)
Thermostable and organic solvent tolerant HZ lipase was an important enzyme which can withstand high temperature and presence of organic solvent for a long period of time. It is an extracellular enzyme secreted by Aneurinibacillus thermoaerophilus strain HZ, which isolated from hot spring in Sungai Kelah, Malaysia. Lipases are part of hydrolytic enzymes and widely use in industrial sectors. In addition, thermostable lipases are expected to play a significant role in industrial processing because running bioprocesses at elevated temperature lead to higher diffusion rate, increase solubility of polymeric substrates in water and reduced risk of contamination. To date, there are no local supplies of lipases even though the market is huge. Therefore, lipases derived from locally isolated microorganism are important in fulfilling the future industrial needs of enzymes. Meanwhile, to use any lipase for industrial application, it is important to purify and characterize the enzyme and study its properties. Thermophilic lipolytic bacteria were screened from several samples collected from hot springs in Batang Kali, Selayang and Sungai Kelah, car service workshop in Port Dickson. The temperature of samples collected ranged from 45ºC to 90ºC. An enrichment culture technique was used to isolate bacteria utilizing olive oil as substrate. Cultures were incubated at 55ºC for 3 days under shaking condition. From the comprehensive screening program for the isolation of thermophilic lipolytic bacteria, 90 positive isolates were obtained on Tributyrin, Rhodamine B, and Triolein agar plates. Twelve isolates demonstrated high lipase activity (0.05-0.2 U/mL). In order to select the best organic solvent tolerant lipase producer, all the twelve isolates were tested for their lipase stability in organic solvents. Four isolates that showed high stability in organic solvent were further investigated in different production media. Isolate A10 was observed to produce the highest level of lipase after 48h incubation and its crude enzyme was stable in the presence of dimethyl sulfoxide (DMSO), chloroform, octanol, dodecanol, and hexadecane. It was identified as Aneurinibacillus thermoaerophilus strain HZ based on its morphological study and 16S rRNA analysis. Further optimization studies were conducted to determine the best lipase production condition. Inoculum size of 7% proved to be the best for lipase production with an optimum temperature of 60ºC when grown under shaking condition of 150 rpm. Among the various natural and synthetic triglycerides used, olive oil served as the best substrate for the production of extracellular lipase with peptone as the best nitrogen source. The cations, Mg2+, Na+, Ca2+ and K+ were found to enhance lipase production. In addition, lipase production was stimulated by Tween 85 as surfactant. The enzyme was purified using two purification steps, anion exchange chromatography and gel filtration. HZ lipase was purified 15.6-fold with specific activity of 43.4U/mg. Purified lipase migrated as a single band with a molecular mass of ~50 KDa on SDS-PAGE. The purified lipase showed high activity at 65 ºC with optimum pH at 7.0. The enzyme was stable from pH 4.0 to 10.0. It also showed high stability with half-life of 4 h 50 min at 60ºC, 3 h 10 min at 65ºC, and 1h 20 min at 70°C. Mg+ and Ca2+ at 28 and 39% respectively, gave an enhancement effect after 15 min of treatment. In addition, 46% increase in enzyme activity was observed after extended incubation (30 min), in the presence of Ca2+. Heavy metal ions such as Cu2+, Fe3+ and Zn2+ inhibited 45% of the HZ lipase activity. Dithiothreitol (DTT) and pepstatin had no effect on the lipase activity, while EDTA and PMSF showed slight inhibitory effect. The lipase exhibited high stability in the presence of dimethylsulfoxide (log P -1.3), methanol (log P -0.76) and n-tetradecane (log P 7.6). HZ lipase showed preference to natural oils as compared to triglycerides and it exhibited the highest activity in the presence of sun flower oil as substrate. In conclusion, a new thermophilic lipolytic bacterium, Aneurinibacillus thermoaerophilus strain HZ, was successfully isolated as a lipase producer and so far no report was available on the isolation of lipase from A. thermoaerophilus. The nucleotide sequence of the bacterium 16S rRNA was deposited at GeneBank under the accession number DQ890194. Optimization studies have resulted in the production of crude enzyme to the level of 0.5 U/mL. HZ lipase was efficiently purified with 19.69% yield and characterization studies have shown its stability and activity at broad range of pH and elevated temperatures. In addition, HZ lipase showed selectivity towards long chain natural oils and stability in the presence of organic solvents. These unique properties will provide considerable potential for many biotechnological and industrial applications.